Animal welfare in swine culture: Review - Pires, Adcléia; Silva, Alanna do Socorro Lima da; Galvão, Andria Tavares GalvãoAndria Tavares; Morais, Adria Fernanda Ferreira de; Mendonça Neto, Jonival Santos Nascimento; Azevedo, Hierro Hasller Freitas de (Pubvet, 2019)
The behavioral change of people regarding the consumption of animal products influences and increases the use of technical sources by rural man, promoting in recently years many changes in productive sector related to research to get better quality products, compromised with social responsibility and sustainability. Currently the consumer becomes extremely exigent because it’s possible to get a lot of information that was not previous and then the consumer would be more interested to knowing the product’s origin and the traceability as well as to know the treatment received by the animal from conception to slaughter. The Brazilian piggery production is among the ten largest exporters worldwide, however, it faces numerous challenges, such as the most important, that is animal welfare due to high value of investments in technologies, management and installations that can promote strategies to improve animal welfare according the European Union regulations. Once regulation do not permit in productive chain using of cages, caudectomy and other management techniques that cause stress to the pigs. In this way, the evaluation of well-being in the swine culture is through the animal behavioral analysis, the physiological responses when the animal leaves their comfort zone, besides the evaluation of production, reproduction and sanity. Therefore, this overview bibliography review aims to analyze how the management influences on quality of pork. This research is to infer that Brazil still needs to advance in the management, installation, transportation and applied technologies to promote animal welfare in swine culture, as well as present low quality indices comparing to the European Union patterns. Then, it will cause loses in the exportation market to Brazil.